Feedback Method of Force Controlled by Electrical Muscle Stimulation Based on Infrared Optical Sensing - Hosono, Satoshi; Miyake, Tamon; Miyake, Shota; Tamaki, Emi (Frontiers in Virtual Reality, 2022)
The goal of the study is to develop a system that can adjust the electrical muscle stimulation parameters for individuals when sharing experiences with stimulation by sensing the degree of muscle contraction during electrical stimulation. If we do not know the appropriate amount of current of stimulation for an individual, the muscles do not contract as we aim and we will not be able to share the experience as we expect. In this study, we present a system estimating fingertip force as output of electrical muscle stimulation by monitoring muscle state based on infrared optical sensing for adjusting electrical muscle stimulation parameters for individual. We developed a regression model based on support vector regression during electrical stimulation using infrared optical sensor with seven people data to estimate the pushing force. The coefficient of determination between the measured pushing force and estimated pushing force was greater than 0.7 and 0.9 for the index and middle fingers, respectively. The system can monitor accurately a feedback value of electrical muscle stimulation fingertip control. The system showed the feasibility of infrared optical sensing for closed-loop feedback control system of the electrical stimulation parameters for individual.